Chemical modification of lignin and thereafter grafting with lactic acid for flexible polymer film preparation. Issue 23 (9th March 2022) - Dutta, Koushik; Singh, Ajit
Abstract: Herein, a green method has been reported to develop highly flexible polymer film from alkali lignin (AL). The AL was firstly chemically modified with epichlorohydrin (ECH) at pH ~9 to synthesize epoxidized lignin (EL). Later, the soft segment was incorporated into the EL by grafting lactic acid (LA), to synthesize lignin‐polylactic acid (Lig‐PLA) copolymer in a solvent‐free condition. Synthesis of EL and Lig‐PLA copolymer was confirmed through Fourier transform infrared spectroscopy, solid‐state 13 C nuclear magnetic resonance, and X‐ray photoelectron spectroscopy analysis. Thermogravimetric analysis and X‐ray diffraction analysis confirmed the increasing total weight (wt) loss and increasing crystallinity for Lig‐PLA copolymer synthesized with increasing LA wt. Polymer film prepared through the hydraulic hot press method showed excellent flexibility for the Lig‐PLA copolymers synthesized with >3 wt ratio of LA with respect to EL. Field emission scanning electron microscopy analysis showed uniform and very smooth surfaces for the Lig‐PLA copolymer film synthesized with >6 wt ratio of LA. These findings demonstrated that flexible polymer film could be achieved through the chemical modification of lignin. Abstract :